2009
DOI: 10.2136/sssaj2008.0208
|View full text |Cite
|
Sign up to set email alerts
|

Crop‐Residue‐Derived Char Influences Sorption, Desorption and Bioavailability of Atrazine in Soils

Abstract: The bioavailability of pesticides in soils is affected by the addition of crop‐residue‐derived char, which alters the sorption and desorption characteristics of the soils. Sorption, desorption, and biodegradation experiments were performed using atrazine [6‐chloro‐N‐ethyl‐N′‐(1‐methylethyl)‐1,3,5‐triazine‐2,4‐diamine] as the target compound in two soils (Hartsells and Grady) with and without a wheat (Triticum aestivum L.) char, and the char alone. The sorption isotherms for both soils were highly linear, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 29 publications
4
50
0
1
Order By: Relevance
“…For the herbicide atrazine, Loganathan et al (2009) reported a decrease in mineralization of the herbicide in the 1% (w/w) wheat char amended soils as compared to the soils slurries, attributing the atrazine bioavailability decrease to the increase in sorption of the herbicide on the char amendment. Guo et al (1991) suggested that atrazine and alachlor degradation could be inhibited by the presence of waste activated carbon, and stimulated by other uncharred amendments, such as municipal sewage sludge and manure.…”
Section: Effect Of Carbonaceous Materials On Pesticide Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the herbicide atrazine, Loganathan et al (2009) reported a decrease in mineralization of the herbicide in the 1% (w/w) wheat char amended soils as compared to the soils slurries, attributing the atrazine bioavailability decrease to the increase in sorption of the herbicide on the char amendment. Guo et al (1991) suggested that atrazine and alachlor degradation could be inhibited by the presence of waste activated carbon, and stimulated by other uncharred amendments, such as municipal sewage sludge and manure.…”
Section: Effect Of Carbonaceous Materials On Pesticide Degradationmentioning
confidence: 99%
“…Wang & Xing (2007) hypothesized that the sorption of organic compounds to un-charred biomass is dominated by absorption mechanisms, whereas adsorption becomes the dominant process with charred materials, largely due to the newly created atomic surfaces and micropores. In the case of wheat char and atrazine, one of the herbicides most used worldwide, the K f value sorption on the amendment was 2012 (Loganathan et al, 2009), and the K f increased by a factor of 5 in a sandy loam soil and of 4.3 in a clay loam soil, when both soils were amended with 1% (w/w) of wheat char. Sorption of pentachlorophenol, an organochlorine compound used as herbicide, insecticide, fungicide, algaecide, and disinfectant, was studied on three soils with different amendments (char, humic acids and peat), by Li et al (2009).…”
Section: Effect Of Carbonaceous Materials On Pesticide Sorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [19] showed that nonpolar and polar aromatic compounds could sorb to the surface of pine needle biochar through partition and/or adsorption depending on the pyrolysis temperature. Loganathan et al [20] reported that application of biochar to soil can significantly increase the sorption of atrazine and, hence, decrease its bioavailability. Chun et al [17] suggested that the relatively high affinity of biochar for polar aromatic compounds (e.g., nitrobenzene) could be attributed to the functional groups (acidity/basicity) on the biochar surface.…”
Section: Introductionmentioning
confidence: 99%
“…C.V. = 20,62%. (YANG e SHENG, 2003;LOGANATHAN et al, 2009). O diuron é pouco móvel no solo, atingindo no máximo a camada de 0-20 cm de profundidade em campo (EL IMACHE et al, 2009) e em coluna (LANDRY et al, 2004), devido ao elevado K oc (145-917 L kg -1 ) (LIYANAGE et al, 2006).…”
Section: Estudos Realizados Porunclassified